2017
DOI: 10.1016/j.tra.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Get on board: Assessing an all-door boarding pilot project in Montreal, Canada

Abstract: Transit agencies often focus on developing strategies aimed at reducing travel time to increase passengers' satisfaction. One strategy used by transit agencies to reduce passenger activity time, and accordingly travel times, is the implementation of all-door boarding -a service allowing transit users to board and alight vehicles through any door. The present study uses data collected in Montreal, Canada, to assess the impacts of an all-door boarding pilot project from two points of view: (1) operationally thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Alternatively, a study which combined holding and stop-skipping strategies found this to be undesirable as such tight controls may induce poorer performance [28]. Perhaps a worthy way forward is to have buses with wide doors or "no doors" [29][30][31], so that multiple passengers may simultaneously board and alight as compared to queuing through a single narrow entry. However, this would risk other issues like fare evasion.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a study which combined holding and stop-skipping strategies found this to be undesirable as such tight controls may induce poorer performance [28]. Perhaps a worthy way forward is to have buses with wide doors or "no doors" [29][30][31], so that multiple passengers may simultaneously board and alight as compared to queuing through a single narrow entry. However, this would risk other issues like fare evasion.…”
Section: Introductionmentioning
confidence: 99%
“…Buses arriving at bus stops in bunches forces commuters to face extended waiting times; and whilst indubitably undesirable, such occurrences are stable [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Bus bunching is a physical phenomenon of a complex socio-technological system.…”
Section: Introductionmentioning
confidence: 99%
“…Although many of the previous work on this subject had identified this problem and the inevitable occurrence of bunching [14-16, 18, 20], we have not encountered an approach based on a physical mechanism for synchronisation of coupled oscillators. Instead, some research dealt with potential strategies towards nullifying bus bunching by holding or delaying some buses, with some extending to adaptive and dynamic controls according to real-time situations [17, 19, 21-23, 29, 31], as well as exploring the effects of buses with wide doors [24,25,30] or engineering the locations of bus stops along the bus routes [27].…”
Section: Introductionmentioning
confidence: 99%
“…e popular method to stabilise the buses' headways is to implement a holding strategy [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] which slows down a fast bus if its headway with respect to the bus ahead of it is deemed to be too small. Other approaches include stop-skipping [11, [22][23][24][25][26] or deadheading (i.e., sending an empty bus directly to a set of designated bus stops) [23,[26][27][28][29], limiting boarding [30][31][32][33][34][35], as well as despatching buses with wide doors [36][37][38].…”
Section: Introductionmentioning
confidence: 99%